Ukrainian and russian borrowings in polish of the petty nobility village of Dorohan in Zhytomyr region - Zakhutska, O. V. (НУБіП України, 2019)
The article presents Ukrainian and/or Russian borrowings used by Poles living in a small petty nobility village in Zhytomyr region in Ukraine in comparison with some other Polish dialects in the same territory.
Українські та російські запозичення у польській мові дрібношляхетського села Дорогань на Житомирщині
У статті представлено українські та/або російські запозичення, вживані у польській мові мешканців невеликого дрібношляхетського села Дорогань у Житомирській області, у порівнянні з лексикою деяких сусідніх польських говірок в Україні.
Keywords: Polish in Ukraine; petty nobility; peasant; borrowing; польська мова в Україні; дрібна шляхта; холоп («селянин»); запозичення